THE INFLUENCE OF JOB PLACEMENT SUITABILITY ON EMPLOYEE ACHIEVEMENT (CASE STUDY AT THE OFFICE OF THE MINISTRY OF RELIGION) SINJAI DISTRICT - Andi Agung Arty; Andi Rustam; Muhammad Akib (International Journal of Economic Research and Financial Accounting, 2024)
This research is a type of quantitative research with the aim of determining the effect of suitability of job placement on employee work performance (case study in the Sinjai Regency Ministry of Religion Office) with a population of 53 employees and a sample of 53 employees. The type of data used in this research is quantitative data obtained from distributed questionnaires and is related to the problem being studied. In this research, the data sources used in data collection include primary data and secondary data. The research instrument used in this research used the Likert Scale method. Based on the results of data research using statistical calculations through applicationsStatistical Package For the Social Science (SPSS) version 23 regarding the Effect of Suitability of Job Placement on Employee Work Performance (Case Study in a Case at the Office of the Ministry of Religion, Sinjai Regency) which was discussed in the previous chapter, the author draws an important conclusion, namely that, in particular, suitability of job placement has a significant positive effect on work performance. employee(Case Study at the Sinjai Regency Ministry of Religion Office). This is shown from the calculation results, namely the regression coefficient value is 0.533 and the significant value is below 0.05, namely 0.000.